THE EFFECT OF GOVERNMENT EDUCATION SPENDING ON ECONOMIC GROWTH THROUGH SCHOOL ENROLLMENT IN INDONESIA - Lestari, Nur Indah (JURNAL INFO ARTHA, 2016)
This paper examines the effect of government spending on education on growth as an indirect process through enrollment rate, specifically in Indonesia. Using a panel data set of 26 provinces from 2000 to 2010 and applying fixed effect approach of panel regression, we find that government spending on education has a positive relationship with enrollment with one-year lag; also, the data show that enrollment affect growth significantly. By enacting the chain rule, government spending on education has a positive effect in economic growth indirectly. Together, these findings suggest that raise government spending on education can increase enrollment rate and enhance economic growth.Â